L14 Inhibition of mitochondrial permeability transition pore (MPTP), by GNX-4728, is beneficial in an in-vitro huntington's disease model. (13th September 2016) - Amico, Enrico; Martinello, Katiusha; Draghi, Federica; Cavalletti, Ennio; Fucile, Sergio; Maglione, Vittorio; Pardo, Alba Di
Abstract : Background: Although Huntington's disease (HD) is not typically considered a mitochondrial disorder, many studies suggest mitochondrial dysfunction as one of the major player in its pathogenesis and candidate it as molecular target for the development of valuable therapeutic treatments for the disease. So far, several mitochondrial-based therapeutic strategies have been designed either at preclinical or at clinical levels, however none of them has been significantly successful. Aims: The purpose of this study was to elucidate the putative role and the mechanistic relevance as well as the validity of dysfunctional mitochondrial permeability transition pore (mPTP) in the pathogenesis of HD with the ultimate aim to clarify whether its modulation might represent a real alternative therapeutic approach for the treatment of this disease. In particular, we investigated whether the administration of GNX-4728, an mPTP inhibitor, already examined in a mouse model of ALS, might be beneficial also in HD. Methods: Anti-apoptotic property of GNX-4728 was explored in a mouse striatal-derived cell model (STHdh) expressing endogenous levels of wild type (STHdh7/7) or mutant (STHdh111/111) Huntingtin. The apoptotic profile and the activation of pro-survival pathways, with or without GNX-4728, was assessed by Annexin V staining and Western Blotting, respectively. Results: Our findings demonstrated that administration of GNX-4728 significantly reduced apoptosis in HD cells. Such a beneficial effect was associated with ameliorated mitochondrial homeostasis and activation of pro-survival Akt and ERK1/2 signalling pathways. Conclusions: Our results strongly support the hypothesis that mPTP may represent a valuable therapeutic target for the development of new and more effective treatment against neuronal dysfunction and cell death occurring in HD.